2022
DOI: 10.3233/hsm-211565
|View full text |Cite
|
Sign up to set email alerts
|

The effect of performance appraisal politics on deviant work behavior: The mediating role of job satisfaction

Abstract: BACKGROUND: Performance management is pivotal in determining employee outcomes. Firms may face undesired consequences in the absence of an impartial and fair performance appraisal system. Organizational justice theory predicts the negative outcomes of performance appraisal politics that the study examines in the form of mediating and outcome variables. OBJECTIVES: There is a paucity of research regarding the impact of justice/fairness perceptions on employee outcomes in the performance appraisal context. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…That is, the appraisee who perceives a high level of performance appraisal politics in the workplace is prone to implement CWB. These findings are consistent with previous research showing a link between performance appraisal politics and employees’ negative behavior ( Naseer and Ahmad, 2016 ; Rosen et al, 2017 ; Sajjad et al, 2017 ; Imran, 2019 ; Imran et al, 2019 ; Tabassum et al, 2021 ; Nagi et al, 2022 ). Although previous studies have confirmed that performance appraisal fairness and satisfaction are negatively associated with CWB ( Colquitt and Zipay, 2015 ; Cohen and Diamant, 2019 ), little research has considered the influence of performance appraisal politics as an antecedent of CWB.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…That is, the appraisee who perceives a high level of performance appraisal politics in the workplace is prone to implement CWB. These findings are consistent with previous research showing a link between performance appraisal politics and employees’ negative behavior ( Naseer and Ahmad, 2016 ; Rosen et al, 2017 ; Sajjad et al, 2017 ; Imran, 2019 ; Imran et al, 2019 ; Tabassum et al, 2021 ; Nagi et al, 2022 ). Although previous studies have confirmed that performance appraisal fairness and satisfaction are negatively associated with CWB ( Colquitt and Zipay, 2015 ; Cohen and Diamant, 2019 ), little research has considered the influence of performance appraisal politics as an antecedent of CWB.…”
Section: Discussionsupporting
confidence: 92%
“…Some researchers have found that employees’ perception of the fairness of and their satisfaction with performance appraisal have a negative relationship with CWB ( Colquitt and Zipay, 2015 ; Cohen and Diamant, 2019 ). Some studies have also explored the profound effect of performance appraisal politics on employee organizational behavior ( Rosen et al, 2017 ; Imran, 2019 ; Naseeb et al, 2019 ; Tabassum et al, 2021 ; Nagi et al, 2022 ), but less attention has been paid to the influence of performance appraisal politics on CWB.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses' workplace deviant behavior will not only reduce their own work efficiency and work involvement [10,11] but also affect their work performance. In addition, it also increases work pressure and turnover intention of colleagues, weakening job satisfaction, organizational commitment and happiness [12][13][14], and affects the stability of the nursing team [15]. On the other hand, deviant behavior will also affect occupational safety, cause medical safety accidents [16], and affect doctor-patient relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have made contributions to the field of workplace deviant behavior, there are still some research gaps. Firstly, previous studies on workplace deviant behavior have mostly focused on inter-enterprise situations [17,18], such as bank employees [14] and construction workers [11], while there is still relatively little research on the workplace deviant behavior of new nurses in medical settings. Secondly, there is a lack of research on the mechanisms of workplace deviant behavior.…”
Section: Introductionmentioning
confidence: 99%